PERLINDUNGAN DAN UPAYA HUKUM BAGI KARYAWAN YANG TERKENA PEMUTUSAN HUBUNGAN KERJA (PHK) SEPIHAK - SENGGI, SRI ANGGITA (Ganec Swara, 2025)
Unilateral termination of employment is a significant issue in industrial relations in Indonesia, which often causes uncertainty for employees. This study aims to analyze the legal protection for employees affected by unilateral layoffs and the legal remedies that can be taken by them. Based on Law No. 13/2003 on Manpower, layoffs must be carried out with valid reasons and following established procedures. This research uses normative juridical method with statutory and conceptual approaches. The results show that employees have the right to severance pay and legal protection from termination actions that are not in accordance with the provisions. Legal efforts that can be made include deliberation, mediation, and if necessary, filing a case with the Industrial Relations Court. Enforcement of these rights is essential to safeguard workers' welfare and create fairer working relationships